Escolarização de alunos com Síndrome de Down: um estudo de caso - Marques, Regiane Rodrigues (2012)
This article presents the results of a case study on the attitude towards the process of schooling, afifteen year old with Down Syndrome. The girl is a student of second year of elementary school ofa public school in the city São Gabriel, Rio Grande do Sul. The theoretical framework consists ofanalysis of literature on the subject. The methodology adopted to direct observation and daily fora month, accompanied by notes in a logbook, the reactions of the young man with DownSyndrome to their schooling process. We report the analysis of the case study, considering theattitudes of student facing situations of learning and action methodology employed to build theirknowledge in an interdisciplinary perspective. The results of this case study show that the girl haddifficulties to spell the letters. However, recognize the entire alphabet, pronouncing it orally. It hasno motor skills to paint and has alternation of humor, and sometimes, very sweet and at othertimes, chafes at ease. The young person needs a personal attendant to assist her in activitiesinside and outside the classroom. There was, also, that the educational activity does not extend inan interdisciplinary way.